Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan PT Artdeco Inti Kreasi Jakarta Timur - Fayza, Roful; Siska, Elmira (Jurnal Bintang Manajemen, 2024)
This research aims to examine the influence of the work environment and work discipline on employee performance at PT Artdeco Inti Kreasi. The research used quantitative methods with 40 employees as respondents. Data analysis includes data quality tests (validity and reliability, classical assumption tests, hypothesis tests and coefficient of determination tests. The results of the analysis show that the work environment does not have a significant effect on employee performance, while work discipline has a significant effect. Work discipline is the variable that has the dominant influence on employee performance. The results of the F test show that simultaneously, work environment and work discipline have a significant effect on employee performance. Analysis of the coefficient of determination shows that work environment factors and work discipline can explain 81.0% of the variation in employee performance. other factors not included in this research. This research provides an understanding of the importance of paying attention to work environment factors and work discipline in improving employee performance in the company.